2010
DOI: 10.4238/vol9-3gmr819
|View full text |Cite
|
Sign up to set email alerts
|

β3-adrenergic receptor polymorphism is related to cardiometabolic risk factors in obese Brazilian subjects

Abstract: ABSTRACT. We determined whether ADRβ3 polymorphism is associated with obesity-related traits in 140 obese patients. Molecular analysis was performed by PCR and RFLP. Individuals carrying the Arg64 allele had a lower waist-to-hip ratio, higher adiponectin and high-density lipoprotein cholesterol levels, and a tendency towards lower blood pressure. In contrast, Trp64/Trp64 carriers were at greater risk for dysmetabolic phenotypes (odds ratio = 2.88, P = 0.03).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
3
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 10 publications
1
2
3
1
Order By: Relevance
“…W64R variation of β-3AR is associated with lower metabolic resting rate, with abdominal obesity, weight gain and difficulty losing weight ( 4 , 5 , 8 , 31 , 32 ). However, these findings have not been confirmed in other studies ( 14 , 15 , 33 ). Interestingly, Genelhu et al ( 14 ) found that obese and hypertensive Brazilian adults with W64/W64 genotypes had elevated fasting plasma insulin levels and higher HOMA-IR scores.…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…W64R variation of β-3AR is associated with lower metabolic resting rate, with abdominal obesity, weight gain and difficulty losing weight ( 4 , 5 , 8 , 31 , 32 ). However, these findings have not been confirmed in other studies ( 14 , 15 , 33 ). Interestingly, Genelhu et al ( 14 ) found that obese and hypertensive Brazilian adults with W64/W64 genotypes had elevated fasting plasma insulin levels and higher HOMA-IR scores.…”
Section: Discussioncontrasting
confidence: 68%
“…However, these findings have not been confirmed in other studies ( 14 , 15 , 33 ). Interestingly, Genelhu et al ( 14 ) found that obese and hypertensive Brazilian adults with W64/W64 genotypes had elevated fasting plasma insulin levels and higher HOMA-IR scores. Such discordant results may be partially explained by ethnicity, age, or population differences in the studied samples.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…ADRB3 trp64arg polymorphism is associated with weight gain, increased visceral fat, abdominal obesity, and difficulty in losing weight [1214151617203435]. However, several studies have reported contradictory results [2122232436]. A recent Brazilian study reported that high HOMA-IR scores and presence of MS are associated with trp/trp genotypes in obese and hypertensive adults [36], and such inconsistencies might be partially explained by ethnicity, age, or population differences in the studied samples.…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies have reported contradictory results [2122232436]. A recent Brazilian study reported that high HOMA-IR scores and presence of MS are associated with trp/trp genotypes in obese and hypertensive adults [36], and such inconsistencies might be partially explained by ethnicity, age, or population differences in the studied samples. In a twin study with a high similarity in genetic and environmental background, the risk of obesity, IR, or type 2 diabetes unexpectedly increased with heterozygosity for ADRB3 trp64arg [37].…”
Section: Discussionmentioning
confidence: 99%